Characterization of NMDAR-Independent Learning in the Hippocampus - Tayler, Kaycie K.; Lowry, Elizabeth; Tanaka, Kazumasa; Levy, Brynne; Reijmers, Leon; Mayford, Mark; Wiltgen, Brian J. (Frontiers in Behavioral Neuroscience, 2011)
It is currently thought that memory formation requires the activation of NMDA receptors (NMDARs) in the hippocampus. However, recent studies indicate that these receptors are not necessary for all forms of learning. The current experiments examine this issue using context fear conditioning in mice. First, we show that context fear can be acquired without NMDAR activation in previously trained animals. Mice trained in one environment (context A) are subsequently able to learn about a second environment (context B) in the presence of NMDAR antagonists. Second, we demonstrate that NMDAR-independent learning requires the hippocampus and is dependent on protein synthesis. However, unlike NMDAR-dependent learning, it is not contingent on the expression of activity-regulated cytoskeleton-associated protein (Arc). Lastly, we present data that suggests NMDAR-independent learning is only observed when recently stimulated neurons are re-activated during conditioning. These data suggest that context fear conditioning modifies synaptic plasticity mechanisms in the hippocampus and allows subsequent learning to occur in the absence of NMDAR activation.